Ontology, Epistemology, Axiology: A New Path to Understanding Tafsir - Moh. Abu Mansur (CV. Publikasi Indonesia, 2026)
This study examines the interpretation (Tafsir) of the Qur’an through the integration of the three main pillars of the philosophy of science—ontology, epistemology, and axiology—as a novel conceptual framework to achieve a more comprehensive and contextual understanding of Qur’anic interpretation. Conventional Tafsir studies have typically focused on textual methodologies such as Tafsir bi al-ma’tsur and Tafsir bi al-ra’yi, with less emphasis on the philosophical foundations concerning the nature of textual existence, the sources and justification of interpretive knowledge, and the embedded values relevant to contemporary issues. The philosophical approach positions Tafsir not merely as a textual interpretive practice, but as an epistemic endeavor that considers the ontological reality of revelation, the epistemological relationship between reason and revelation, and the axiological implications of hermeneutics within modern social contexts. Using a qualitative descriptive method based on critical literature analysis from primary and secondary sources in Tafsir and philosophy of science, the findings demonstrate that this integrative framework bridges classical Tafsir traditions with the interpretive demands of the present era and expands Tafsir into a multidisciplinary and socially relevant field. The study’s contribution lies particularly in emphasizing the axiological dimension as a crucial aspect of Tafsir studies that not only interprets the text but also directs its values toward practical implementation in the social life of both the Muslim community and broader society.